ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN DI MIUBEL PUTRI BARITO MUARA TEWEH - Sofia SOFIA (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2026)
The purpose of this study was to analyze the marketing strategies implemented, to determine the sales conditions, to identify the marketing strategy factors that influence sales, and to formulate appropriate marketing strategies to increase sales at Miubel Putri Barito Muara Teweh. This study used a descriptive qualitative approach. The research subjects consisted of the business owner, employees, and consumers of Miubel Putri Barito Muara Teweh totaling 10 informants selected using purposive sampling technique. Data were collected through interviews, observation, and documentation using interview guidelines as research instruments. Data analysis used the interactive analysis model of Miles and Huberman which includes data reduction, data display, and conclusion drawing. The results showed that the marketing strategy implemented at Miubel Putri Barito has applied the elements of the marketing mix including product, price, place, promotion, people, process, and physical evidence. Sales conditions showed a fairly good development marked by increasing sales volume, revenue, sales growth, achievement of sales targets, and the number of customers. Factors influencing sales include product quality and variety, appropriate pricing, strategic location, informative promotion, good employee service, simple service processes, and a clean and comfortable business environment. Appropriate marketing strategies to increase sales include maintaining product quality, increasing product variety, maintaining competitive prices, improving promotions especially through social media, improving service quality, and maintaining the comfort of the business place.